Research trends on causes of Kawasaki disease in the COVID-19 era: focus on viral infections - Young Hwan Lee (The Korean Pediatric Society, 2023)
Despite studies on the etiology of Kawasaki disease (KD) ongoing for half a century since its discovery, its cause has not yet been clearly identified. Although the clinical, epidemiological, and pathophysiological characteristics of KD are presumed to be closely related to infectious diseases, studies of various pathogens to identify its etiology have been actively conducted. To date, bacteria, fungi, and viruses have been investigated to determine the relationship between KD and infection, among which viruses have attracted the most attention. In particular, during the coronavirus disease 2019 pandemic, there were many reports in Europe of a sharp increase in cases of Kawasaki-like disease (KLD), while conflicting reports that the prevalence of KD decreased due to thorough "social distancing" or "wearing mask" in Asian countries drew more attention regarding the association between KD and viral infection. Therefore, the differential diagnosis of KD from KLD with these similar spectra has become a very important issue; simultaneously, research to solve questions about the association between KD and viral infections, including sudden acute respiratory syndrome coronavirus 2, is drawing attention again. Moreover, a new concept has emerged that immune responses occurring in patients with KD can be caused by the pathogen itself as well as host cells damaged by infection. This paper summarizes the research trends into KD etiology and related pathophysiology, especially its association with viral infections, and present future research tasks to increase our understanding of KD.